Clinical Study of NeuroRegen Scaffold Combined with Human Mesenchymal Stem Cells for the Repair of Chronic Complete Spinal Cord Injury. Issue 5 (May 2017) - Zhao, Yannan; Tang, Fengwu; Xiao, Zhifeng; Han, Guang; Wang, Nuo; Yin, Na; Chen, Bing; Jiang, Xianfeng; Yun, Chen; Han, Wanjun; Zhao, Changyu; Cheng, Shixiang; et al.
Regeneration of damaged neurons and recovery of sensation and motor function after complete spinal cord injury (SCI) are challenging. We previously developed a collagen scaffold, NeuroRegen, to promote axonal growth along collagen fibers and inhibit glial scar formation after SCI. When functionalized with multiple biomolecules, this scaffold promoted neurological regeneration and functional recovery in animals with SCI. In this study, eight patients with chronic complete SCI were enrolled to examine the safety and efficacy of implanting NeuroRegen scaffold with human umbilical cord mesenchymal stem cells (hUCB-MSCs). Using intraoperative neurophysiological monitoring, we identified and surgically resected scar tissues to eliminate the inhibitory effect of glial scarring on nerve regeneration. We then implanted NeuroRegen scaffold loaded with hUCB-MSCs into the resection sites. No adverse events (infection, fever, headache, allergic reaction, shock, perioperative complications, aggravation of neurological status, or cancer) were observed during 1 year of follow-up. Primary efficacy outcomes, including expansion of sensation level and motor-evoked potential (MEP)-responsive area, increased finger activity, enhanced trunk stability, defecation sensation, and autonomic neural function recovery, were observed in some patients. Our findings suggest that combined application of NeuroRegen scaffold and hUCB-MSCs is safe and feasible for clinical therapy in patients with chronic SCI. Our study suggests that construction of a regenerative microenvironment using a scaffold-based strategy may be a possible future approach to SCI repair.